Impact of methylprednisolone in priming solution of cardiopulmonary bypass on anti-inflammatory CD163 receptor during cardiac surgery - Krejsek, J; Mandak, J; Kunes, P; Lonsky, V; Kolackova, M; Jankovicova, K; Andrýs, Ctirad (Perfusion, 2012)
We evaluated the influence of methylprednisolone in cardiopulmonary bypass fluid on scavenger receptor for hemoglobin CD163 molecule expression on monocytes of patients who underwent elective coronary artery bypass grafting with cardiopulmonary bypass with either exposure to methylprednisolone present in the cardiopulmonary bypass fluid (20 patients), or without methylprednisolone in the cardiopulmonary bypass fluid (22 patients) and operated on without cardiopulmonary bypass (42 patients). The dynamics of CD163 expression was also followed in patients operated on without cardiopulmonary bypass. This study was a retrospective analysis of a comparison of two studies. The expression of CD163 was determined quantitatively by standardized flow cytometry technique. The similarities in the dynamics of CD163 monocyte expression, comparing the patients operated on with or without cardiopulmonary bypass, were found. Compared to the preoperative level, CD163 monocyte expression was significantly elevated on the 1(st) postoperative day. Monocyte CD163 expression on the 1(st) postoperative day was evidently similar in both groups of patients operated without cardiopulmonary bypass (median value of mean fluorescence intensity (MFI) 18,896; interquartile range from 27,538 to 57,711; median value of MFI 18,863; interquartile range from 16,514 to 26,559; n.s.), suggesting high reproducibility of our flow cytometric method; the monocyte CD163 expression was significantly higher (median value of MFI 37,902; interquartile range from 27,538 to 57,711) on the 1(st) postoperative day in patients exposed to methylprednisolone compared to patients without this exposure (median value of MFI 20,995; interquartile range from 16,321 to 29,623) (p<0.001). We concluded that the expression of hemoglobin scavenger receptor CD163 on monocytes of cardiac surgical patients is induced by methylprednisolone present in cardiopulmonary bypass fluid.
Keywords: senioři; methylprednisolon; pooperační období; Postoperative Period; antiflogistika; Methylprednisolone; antigeny diferenciační myelomonocytární; Receptors, Cell Surface; Gene Expression Regulation; mužské pohlaví; Monocytes; Antigens, Differentiation, Myelomonocytic; koronární bypass; regulace genové exprese; Coronary Artery Bypass; monocyty; ženské pohlaví; Anti-Inflammatory Agents; Humans; kardiopulmonální bypass; Antigens, CD; receptory buněčného povrchu; Cardiopulmonary Bypass; Female; Aged; CD antigeny; lidé; Male